2016
DOI: 10.1080/01635581.2017.1247888
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Testing the Effects of Eating Frequency on Two Hormonal Biomarkers of Metabolism and Energy Balance

Abstract: Background Eating frequency may influence obesity-related disease risk by attenuating post-prandial fluctuations in hormones involved in metabolism, appetite regulation, and inflammation. Materials/Methods This randomized crossover intervention trial tested the effects of eating frequency on fasting plasma insulin-like growth factor-I (IGF-1) and leptin. Fifteen participants (4 males, 11 females) completed two eucaloric intervention phases lasting 21 days each: low eating frequency (“low-EF”; 3 eating occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Perrigue et al [ 81 ] investigated the effect of eating frequency on metabolic markers in subjects without obesity. Meals/day frequencies were negatively correlated with serum IGF-1 levels, but no associations were found for leptin levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perrigue et al [ 81 ] investigated the effect of eating frequency on metabolic markers in subjects without obesity. Meals/day frequencies were negatively correlated with serum IGF-1 levels, but no associations were found for leptin levels.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that changes in leptin are independent of circadian rhythms and stress factors; however, the endogenous modulation of leptin might be essential in preventing various chronic metabolic and brain diseases [ 56 , 73 , 75 , 78 , 81 ]. Therefore, it is necessary to understand the physiology of leptin and a healthy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol specified that total energy and macronutrient distribution were to be kept constant on both study arms. We found that compared with the grazing pattern, the meals pattern led to significantly higher serum insulin-like growth factor 1, which is secreted in response to an insulin stimulus ( 46 ). Taken together, the data to date are not consistent.…”
Section: Discussionmentioning
confidence: 97%
“…Heden et al ( 21 ) reported that the incremental AUC for insulin was significantly larger following a 3 meal per day experimental condition in 8 obese women compared to a 6 meal per day condition. We previously reported a randomized crossover trial comparing meals (eating 3 times per day) with grazing (eating 8 times per day) ( 46 ). A registered dietitian gave detailed guidance to study participants as they prepared and consumed their own meals throughout the 2 study periods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have designed and implemented a randomized controlled trial in healthy, free-living individuals that will test the effect of EF on blood-based biomarkers of inflammation, adiposity and satiety. These outcomes were selected based on our prior pilot work [ 11 , 12 ] as well as that of others [ 4 , [13] , [14] , [15] ]. Here we describe the study design and protocol.…”
Section: Introductionmentioning
confidence: 99%